Proposing the new parclo progressA design as a substitute for the conventional partial cloverleaf A interchanges. (4th July 2021) - Mehrara Molan, Amirarsalan; Hummer, Joseph E.
ABSTRACT: This paper proposes a new design called a partial cloverleaf progressA (parclo progressA) which could be considered as a substitute for failing conventional parclo A interchanges. Over 200 VISSIM simulation tests were conducted to make a comparison between the new parclo progressA and the conventional parclo A in terms of traffic operation. Also, the same tests were conducted in the Surrogate Safety Assessment Model to evaluate the safety performance of the designs. According to the results, the parclo progressA performed better than the conventional parclo A in terms of both traffic operation and traffic safety. The mean travel time in the parclo progressA with 2-phase signlas was significantly lower than the parclo A, especially when there are high turning traffic demands. Regarding the safety performance, the parclo progressA had about 25% fewer simulated conflict interactions compared to the parclo A with dual left turn lanes from the off-ramps.